ANALISA COST SHARING PERHITUNGAN TARIF HEMODIALISIS (HD) MASYARAKAT MISKIN DI RUMAH SAKIT UMUM PKU MUHAMMADIYAH UNIT I YOGYAKARTA - Primandita, .; Marwati, Triyani; Solikhah, . (Universitas Ahmad Dahlan, 2011)
Background: Growing and expanding hopital may be efficiently and effectively managed, it is requiredto be conducted to face the tight competition in world of health service. If the hospital wish to survive in the competition, they need to recount the existing hospital tariff previously, that is by using competitive tariff model calculation. Hospital of PKU Muhammadiyah Unit I Yogyakarta divides HD tariff into two parts, these are Single Use and Re Use tariff. There are cost sharing differences between HD tariff in hospital and government. In this research, the reseacher only focuses on HD tariff of Re Use in order to reduce cost sharing. All this time, the hospital has never counted different cost. It can create lose for the hospital. th s researcher interest to analyze the cost sharing of hemodialisis tariff calculation for poor in public hospital of PKU Muhammadiyah Unit I Yogyakarta. Methode: This research type is descriptive research qualitative which analyzed real expense by using real cost methode and difference which is burdened by patien toward real tariff, meanwhile opinion about cost sharing is taken by interview with superintendent finance and superintendent of hemodialisis unit using interview method. Resulth: this research show the real tariff equal to Rp.912.571 while tariff released by hospital equal to Rp.575.000, and difference between second tariff is Rp.337.751, while tariff given by government is Rp.528.067 and difference with the real tariff equal to Rp.384.684. Conclusion: that unit based cost tariff higher than tariff given by hospital at this time, the biggest expense is component for examines or substance used up wear. The hospital should determine the strategy to decrease the difference. Key Words: cost sharing, real cost method, tariff packet, hemodialisis, poor, society